Improvement of regenerative rankine cycle using absorption heat boosters - Mali, Nilesh A.; Mudadi, Rohit H.; Bhagwat, Sunil S. (International Journal of Exergy, 2013)

Comparative analysis of extractive and pressure swing distillation for separation of THF-water separation - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Computers & Chemical Engineering, 2017)
In the present work, extractive and pressure-swing distillation methods are analyzed in detail through steady state ASPEN Plus simulations to propose the most economic method for separation of equimolar mixture of THF-Water. Various solvents were evaluated and DMSO was identified as the most appropriate solvent, as it gave minimum Total Annual Cost (TAC) for desired purity. In case of pressure swing distillation, various pressure ranges were explored to achieve minimum TAC. Configurations for extractive and pressure swing distillation with heat integration were also worked out. The optimum designs of extractive and pressure swing distillation with and without heat integration were compared on a common basis of feed conditions and purity constraints. Results indicate that TAC of extractive distillation with heat integration is 5.2% less than that of PSD with partial heat integration. (C) 2017 Elsevier Ltd. All rights reserved.

Study of the effect of operating parameters on the extractive distillation of isopropyl alcohol–water mixture using dimethyl sulphoxide as an entrainer - Ghuge, Pravin D.; Mali, Nilesh A.; Sirsam, R. S. (Indian Chemical Engineer, 2017)
Abstract: In this paper, the simulation analysis of separation of isopropyl alcohol (IPA)–water via extractive distillation by using dimethyl sulphoxide as an entrainer is presented. The steady-state simulation for this process was done using Aspen Plus simulator. The aim of this work is to study the effect of various operating parameters such as number of stages, molar reflux ratio, binary feed stage number, entrainer feed stage number, temperature of entrainer feed and entrainer to feed molar ratio on the purity and energy consumption. The sensitivity of these parameters serves as a basis to choose the optimum operating conditions to maximize the IPA purity and minimize the energy requirement. In this analysis, among various operating parameters, those which directly affect the IPA purity and the parameters which affect the reboiler duty, for the given separation task, are identified. Simulation results with optimum operating conditions and their economic analysis are also presented.
Keywords: Aspen Plus Simulators; Azeotrope; Computer software; Distillation; Energy requirements; Energy utilization; Extractive distillation; Isopropyl alcohol/water; Isopropyl alcohols; Operating parameters; Optimum operating conditions; Sensitivity analysis; simulation; SimulationSteady-state simulations; Solvents

Vapor-liquid equilibrium data for binary mixtures of acetic acid plus anisole, acetone plus anisole, and isopropanol plus anisole at pressure 96.15 kPa - Mali, Nilesh A.; Mali, Pawan K.; Patil, Asmita P.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2017)
In this work, the vapor-liquid equilibrium (VLE) data have been generated at the local atmospheric pressure of 96.15 kPa for the binary systems acetic acid + anisole, acetone + anisole, and isopropanol + anisole. A circulation type apparatus was designed and developed with few modifications in one of the stills proposed in the literature. For the validation of the new apparatus, VLE data were generated for the known system of N,N-DMF + aniline and compared with the literature data. The VLE data, generated in Txy form for all pairs, were found to be consistent through the point-to-point consistency test. Activity coefficient models, Wilson, NRTL, and UNIQUAC, were fitted to these data using an objective function of minimizing the sum of deviation between experimental and calculated total pressures to estimate the binary interaction parameters. The model predictions with estimated parameters were compared with the experimental data and found appropriate.

Vapor-liquid equilibrium data for binary mixtures of dimethyl carbonate with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate at 93.13 kPa - Mali, Nilesh A.; Yadav, Satyajeet S.; Ghuge, Pravin D.; Joshi, Sunil. S. (Journal of Chemical and Engineering Data, 2017)
Isobaric vapor-liquid equilibrium (VLE) data was measured at the local atmospheric pressure of 93.13 kPa for the binary systems of dimethyl carbonate (DMC) with methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, and isoamyl acetate using a dynamic recirculation still. VLE data was generated in the form of T-x,y and was checked for thermodynamic consistency using the Herington area test, Van Ness test, and mean absolute deviation between experimental and calculated total pressure and vapor phase composition. Data for all pairs meet the criteria for thermodynamic consistency and were found suitable for process modeling. Binary interaction parameters for the Wilson, nonrandom two-liquid (NRTL), and universal quasichemical (UNIQUAC) activity coefficient models were determined using the objective function of minimizing the deviation between the experimental and the calculated vapor phase composition and total pressure. For all binary systems, Wilson, NRTL, and UNIQUAC models gave good predictions. Azeotropic behavior was observed for the isopropyl acetate-DMC pair at 357.8 K and 0.6 mole fraction of isopropyl acetate.

Isobaric vapor-liquid equilibrium data for binary systems of anisole with methyl acetate, ethyl acetate, n-propyl acetate, and isopropyl acetate at 93.9 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
The present work reports experimental isobaric vapor-liquid equilibrium data at 93.9 kPa pressure using a dynamic recirculation still for four binary pairs of acetates with anisole. The suitability of the experimental data for modeling was established by performing the Herington area test, Van Ness test, and mean absolute deviation test. Binary interaction parameters necessary for process modeling were derived through the regression of the VLE data for Wilson, NRTL, and UNIQUAC activity coefficient models with a suitable objective function. VLE data in the form of T-x, y plots indicates no formation of azeotropes for all pairs.

Refractive index and vapor-liquid equilibrium data for the binary systems of anisole with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2018)
Phase equilibrium behavior of binary systems of anisole with xylene isomers was analyzed experimentally. An apparatus which establishes equilibrium conditions through continuous circulation of equilibrium vapor condensate and equilibrium liquid was used. Experimental data comprising refractive indices of binary mixtures, equilibrium compositions of vapor and liquid, and equilibrium temperature are reported for all binary systems. Thermodynamic consistency of vapor-liquid equilibrium data was established for using the Herington, Van Ness and absolute mean deviation tests. Interaction parameters of activity coefficient models, Wilson, nonrandom two liquid, and universal quasichemical, which are important for accounting nonideal behavior in process modeling, are also estimated through regression of the respective binary VLE data. Although VLE data shows that binary systems are nonazeotropic in nature, a pinch in the T-x,y plot indicates that separation of all binary system using distillation may need a significant number of stages.

Experimental investigation of isothermal vapor-liquid equilibrium and estimation of excess thermodynamic properties (h(E)) of CHO2K-H2O from 278.15 to 423.15 K - Takalkar, Gorakshnath D.; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (Journal of Chemical and Engineering Data, 2019)
In this paper, vapor liquid equilibrium (VLE) of a binary mixture, potassium formate-water (CHO2K-H2O), was measured experimentally using a dynamic moving type VLE setup in the temperature range of 313.15 to 393.15 K. Overall, large vapor pressure data points generated for the mole fraction of CHO2K from 0.023 to 0.461 and the solution temperature up to 423.15 K were used to correlate the local composition-based activity coefficient model (NRTL model). The data obtained via the thermodynamic model fitting shows good agreement with the experimental VLE data with overall average relative deviation of 2.15% and root-mean-square deviation of 0.25%. The obtained results further indicate that the binary mixture exhibits a negative deviation from the Raoult's law, which is an important characteristic of the working fluid used for a heat-activated vapor absorption system (VAS). Therefore, the CHO2K-H2O mixture can be considered as an alternative working pair that will overcome the limitations allied to the crystallization and corrosion of the commercial working fluids mainly lithium bromide-water (LiBr-H2O). The fitted nonrandom two-liquid model was further utilized to determine the excess thermodynamic properties, solution enthalpy, solution entropy, and equilibrium P-T-x (Duhring) plot.

Energetic and exergetic performance of NH3-H2O-based absorption refrigeration cycle: effect of operating factor - Takalkar, Gorakshnath Dadabhau; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (International Journal of Exergy, 2020)
One of the major objectives while designing the vapour absorption refrigeration system (VARS) is to acquire better performance within the accessible heat source and sink temperature limit. In this paper, attempts are made to identify the temperature limit for the optimisation of a single stage ammonia refrigeration system (AAR) by performing a thermodynamic analysis. To estimate the potential of utilisation of low-grade heat energy, operating factor (R) is considered towards optimising the energetic (COP) and exergetic COP (ECOP). The simulated COP and ECOP results are expended to predict the feasibility and optimum operating region for an AAR cycle in terms of theRand various operating temperatures such asT(gen),T-abs,T-cond,T-e. The operating factorRcovers a wide range of applications i.e., from deep-freezing (253.15 K) to air conditioning (283.15 K) and from water-cooling (303.15 K) to air cooling (318.15 K).
Keywords: AAR; ammonia absorption refrigeration; cold storage; exergy; operating factor; solar energy

Experimental analysis of vapour-liquid phase equilibria for binary systems of diethyl carbonate with methyl, ethyl, isopropyl, n-butyl and isoamyl acetates at 95 kPa - Bhoi, Bharat R.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical Thermodynamics, 2020)
Experimental analysis of vapour-liquid phase equilibrium (VLE) for five binary pairs of diethyl carbonate (DEC) with methyl acetate, ethyl acetate, isopropyl acetate, n-butyl acetate and isoamyl acetate was carried out in this study. VLE data were generated experimentally at local atmospheric pressure of 95 kPa in a glass dynamic recirculation still. Reliability of data was checked with the thermodynamic consistency tests by Van Ness, infinite dilution, pure component and mean absolute deviation test. Experimental data was found to be thermodynamically consistent with all tests and data was regressed with Wilson, NRTL and UNIQUAC activity coefficient models to determine binary interaction parameters. Binary pair of DEC with n-butyl acetate has shown azeotropic behaviour with minimum boiling azeotrope and a close boiling behaviour through-out the composition range. No azeotropic behaviour was observed for the rest of the binary pairs. (c) 2020 Elsevier Ltd.
Keywords: Diethyl carbonate; ethyl acetate; Isobaric; Isopropyl acetate; methyl acetate; VLE

Experimental vapor-liquid phase equilibrium analysis of the binary systems of aniline with xylene isomers at 93.13 kPa - Yadav, Satyajeet S.; Mali, Nilesh A.; Joshi, Sunil S. (Journal of Chemical and Engineering Data, 2020)
In the present work, vapor-liquid phase equilibrium (VLE) analyses of binary systems of aniline with four isomers of xylene, comprising p-xylene, m-xylene, o-xylene, and ethylbenzene, are reported at 93.13 kPa. The experimental VLE data was generated in a dynamic circulating vapor-liquid, and the data was found thermodynamically consistent using the Van Ness point-to-point consistency test. The experimental VLE data was regressed with the Wilson, NRTL, and UNIQUAC activity coefficient models to obtain the binary interaction parameters. No azeotropic or close-boiling behavior was observed in any of the binary pair, and these pairs were found suitable for separation through a conventional distillation method.

Extractive distillation configuration for nitric acid dehydration using sulfuric acid as a solvent - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Industrial & Engineering Chemistry Research, 2020)
In this work, an extractive distillation configuration for dehydration of nitric acid is proposed with sulfuric acid as a solvent. Thermodynamic modeling of the vapor-liquid equilibrium of binary and ternary systems of nitric acid/water/sulfuric acid is carried out using the electrolyte non-random two-liquid (eNRTL-RK) thermodynamic property method in the Aspen plus process simulator. The model performance is validated by comparing the experimental data with the estimated data by the eNRTL-RK model and is found to be in good agreement. The thermodynamic model is then used for developing a triple-column extractive distillation sequence, comprising a preconcentration column, an extractive distillation column, and a solvent recovery column. The configuration is designed, simulated, and optimized to concentrate dilute nitric acid using sulfuric acid as a solvent to break the nitric acid-water azeotrope. The operating and structural parameters of the distillation configuration are optimized simultaneously with an objective of minimizing the energy consumption and the total annual cost (TAC) of the overall configuration.

Intensified reactive distillation configurations for production of dimethyl ether - Gor, Nikhil K.; Mali, Nilesh A.; Joshi, Sunil S. (Chemical Engineering and Processing-Process Intensification, 2020)
The combustion properties of dimethyl ether (DME) are similar to the conventional fuels; hence it is being used as a promising green energy source. The conventional method of DME production by methanol dehydration is highly energy consuming due to the use of a series of distillation columns. In the present study, an energy efficient reactive distillation configuration is proposed for DME production which leads to higher methanol conversion with less energy requirement as compared to reported configurations. The reactive distillation (RD) and dual reaction zone reactive divided wall column (RDWC) were analyzed using steady state ASPEN simulations. Subsequently, all the design parameters were optimized by sensitivity analysis to minimize the Total Annual Cost (TAC) of the configuration. The results showed that the RD column is more energy efficient than RDWC as it requires 10.68 % less TAC. The proposed RD and dual reaction zone RDWC configurations were found to have less specific energy requirements and less cost per kg of DME than any other configuration reported earlier.
Keywords: Energy efficient configuration; Reactive distillation; Reactive divided wall column; Total annual cost

Selective monoalkylation of hydroquinone in the presence of SO3H-functionalized ionic liquids as catalysts - Bhongale, Priyanka V.; Joshi, Sunil S.; Mali, Nilesh A. (Chemical Papers, 2020)
A process aiming atO-alkylation of hydroquinone (HQ), where ionic liquids (ILs) act as catalyst is objectively described. Five SO3H-functionalized ILs having different cations were prepared and characterized by NMR and FTIR techniques. The acidity and thermal stability of ILs were determined by Hammett function and thermogravimetric analysis (TGA), respectively. The catalytic activity of these ILs were tested forO-alkylation of HQ with methanol in 4-methoxyphenol (4MP) in the presence of small amount of benzoquinone (BQ). The effect of reaction parameters such as temperature, time, catalyst loading and substrate concentration on the conversion of HQ and product distribution was examined and optimized to maximize the yield of 4MP using 1,3-disulfonic acid imidazolium hydrogen sulfate (IL2) catalyst. Maximum yield of desired product 4MP 93.79% was obtained at 338 K temperature, 5.45 x 10(-2) mol HQ, 8.33 x 10(-3) mol BQ, and 10.37 mol% catalyst loading in 120 min reaction time. Single-product formation was observed up to 338 K temperature but higher temperature (above 338 K) and longer reaction time resulted in the formation of 2,4-dimethoxyphenol (24DMP) as a by-product. Catalyst recyclability was also established up to the fifth run which showed no declination in its activity.
Keywords: 4-Methoxyphenol; Benzoquinone; Hydroquinone; ionic liquids; O-alkylation

Effect of CaCl2 and ZnCl2 salts on isobaric vapor-liquid equilibrium in separation of the azeotropic mixture of ethanol plus water - Ghuge, Pravin D.; Mali, Nilesh A.; Joshi, Sunil S. (Fluid Phase Equilibria, 2021)
Present work analyzes potential of calcium chloride (CaCl2) and zinc chloride (ZaCl(2)) salts as entrainer for breaking the minimum boiling azeotrope of ethanol and water. Isobaric vapor-liquid equilibrium (VLE) data for the binary systems of water + ethanol and ternary system of water + ethanol + calcium chloride, and water + ethanol + zinc chloride were measured at a constant pressure of 94.5 kPa. The effect of salts on the relative volatility of ethanol to water as well as on the vapor phase mole fractions of ethanol were also studied experimentally. From the experimental results, it is observed that with addition of salts, the azeotropic point of the ethanol and water system can be eliminated. Salting out effects in case of calcium chloride was more than that zinc chloride salt. The results obtained in this work showed that calcium chloride could be a better choice for separation of the water + ethanol azeotrope. Electrolyte nonrandom two-liquid (eNRTL) model was used to correlate the experimental VLE data. The model prediction with the regressed parameters was found in well agreement with the experimental data. The experimental data obtained in this work was found thermodynamically consistent using van Ness test. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Azeotrope; eNRTL; Ethanol; salts; Vapor-liquid equilibrium; Water

Kinetic study on alkylation of hydroquinone with methanol over SO3H functionalized Bronsted acidic ionic liquids - Bhongale, V. Priyanka; Amonkar, Amogh A.; Joshi, Sunil S.; Mali, Nilesh A. (Canadian Journal of Chemical Engineering, 2022)
O-alkylation of a dihydric phenol (i.e., hydroquinone) with methanol in presence of benzoquinone catalyzed by double SO3H functionalized Bronsted acidic ionic liquids (i.e., 1,3-disulphonic acid imidazolium hydrogen sulphate, 1,3-disulphonic acid benzimidazolium hydrogen sulphate, and sulphuric acid) is studied in a batch reactor. The sensitivity of activity and selectivity with reaction time, temperature, speed of agitation, and catalyst loading was examined. The plausible reaction pathways proposed based on the experimental observations and detailed kinetic investigation are performed by assuming a homogeneous reaction phase. The kinetic parameters, such as pre-exponential factor and activation energy, are estimated for both ionic liquids and sulphuric acid by considering all competitive reactions, and comparative results were presented. An extended form of the Arrhenius equation is used to estimate the kinetic parameters for the reaction which showed curvature in lnk against a 1/T plot. The model prediction with the estimated kinetic parameters is in good agreement with the experimental data, which confirmed the model validity in the experimental operating range. It was found that ionic liquid has a potential application in the synthesis of a selective monoalkylated product of hydroquinone. The kinetic analysis performed is found to be useful in the understanding of process behaviour.
Keywords: 4-Methoxyphenol; Hydroquinone; ionic liquids; Kinetic analysis; O-alkylation

Reduction of carbon dioxide to dimethylformamide using ruthenium doped Mg/Al hydrotalcites under supercritical conditions - Chaudhary, Sagar D.; Rahatade, Shardul S.; Joshi, Sunil S.; Mali, Nilesh A. (Journal of CO2 Utilization, 2022)
The utilization of carbon dioxide is one of the developing areas due to its significant contribution to global warming. Reducing carbon dioxide (CO2) to formic acid and its derivatives has gained importance because of its thermodynamic limitations and high industrial demand. In this article, we report the synthesis of dime-thylformamide (DMF) using ruthenium doped Mg/Al calcined hydrotalcite by CO2 hydrogenation in the presence of dimethylamine (DMA). At optimized conditions, complete conversion of dimethylamine was achieved with more than 92% product yield at 170 degrees C and 13 MPa pressure with a reaction time of 6 h. Key catalyst properties were determined using X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), CO2-temper-ature programmed desorption (TPD), H-2 temperature-programmed reduction (TPR) and Fourier transform infrared (FTIR). The determination of surface morphology was carried out using field emission scanning electron microscope (FE-SEM) and high-resolution transmission electron microscopy (HR-TEM). At the same time, the chemical composition was verified by energy-dispersive X-ray (EDS). In addition, kinetic modeling is performed using the two site Langmuir-Hinshelwood-Hougen-Watson model. The regressed kinetic parameters gave an appropriate fit with experimental concentration values and activation energy is calculated as 413 kJ/mol K-1.
Keywords: Dimethylformamide; Hydrogenation; hydrotalcite; Langmuir-Hinshelwood-Hougen-Watson model; Supercritical carbon dioxide

Reusable and efficient polystyrene immobilized ionic liquid catalyst for batch and flow methylation of hydroquinone - Bhongale, V. Priyanka; Joshi, Sunil S.; Mali, Nilesh A. (Catalysis Letters, 2022)
An environmentally benign process for synthesizing 4-methoxyphenol through methylation of hydroquinone using polystyrene immobilized Bronsted acidic ionic liquid is presented. The catalyst has been characterized by several techniques, such as solid-state NMR, FTIR, and XRD. The morphological properties were analyzed through SEM and TEM analysis. The elemental analysis was performed using EDS and XPS techniques. The catalyst was thermally stable up to 603 K, which was confirmed by TGA. The chemical interaction between ionic liquid and polystyrene was confirmed by measuring the glass transition temperature of pure polystyrene and catalyst. The BET analysis was performed to estimate the catalyst's surface area, pore size, and pore volume. The recyclability of the proposed new catalyst was established up to five recycle runs in the batch mode. In addition, continuous flow experiments were conducted to test the catalytic activity in terms of catalyst life span and showed excellent stability up to 20 h. The rapid separation, long-term stability, and efficient recycling of synthesized polymeric catalysts make an excellent alternative to the commonly used homogeneous catalysts for selective O-methylation of hydroquinone reaction. The newly developed continuous process for synthesizing 4-methoxyphenol with 100% selectivity suggests good opportunities to reduce energy consumption, which designates a cost-effective process. [GRAPHICS] .
Keywords: 4-Methoxyphenol; Hydroquinone; O-methylation; Polystyrene immobilized ionic liquid

Subcritical water hydrolysis of N-acetyl-D-glucosamine: hydrolysis mechanism, reaction pathways and optimization for selective production of 5-HMF and levulinic acid - Kulkarni, Sphurti Prakash; Dure, Shital N.; Joshi, Sunil S.; V. Pandare, Kiran; Mali, Nilesh A. (Carbohydrate Research, 2022)
In this study, the subcritical water hydrolysis of N-acetyl-D-glucosamine (NAG), a monomer of abundant renewable marine biopolymer chitin, for production of value-added chemicals is investigated. The enhanced ionization of water at subcritical conditions (200 degrees C; 50-100 bar), provides enough acidity for deacetylation of NAG resulting in 80% yield of acetic acid along with traces of formic acid, lactic acid, glucose, fructose, 5hydroxymethylfurfural (5-HMF),etc. The significant humin formation indicates that the self-condensation and polymerisation of 5-HMF is favored in water at subcritical conditions. A catalyst p-toluenesulfonic acid (p-TsOH) was employed to selectively convert NAG to levulinic acid (LA) via ring opening of 5-HMF previously formed during hydrolysis. The maximum yield of 27.13 +/- 1% and 53.46 +/- 1% of 5-HMF and LA, respectively, was obtained at process conditions optimized using Box-Behnken design coupled with response surface methodology. Subcritical water enables greener conversion of NAG to platform chemicals wherein the selective production can be achieved by tuning the process conditions.
Keywords: 5-Hydroxymethylfurfural; chitin; Glucosamine; levulinic acid; Response surface methodology; Subcritical water

Performance of Li exchange hierarchical X zeolite for CO2 adsorption and H2 separation - Shrotri, Aadesh R.; Birje, Amit R.; Niphadkar, Prashant S.; V. Bokade, Vijay; Mali, Nilesh A.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2024)
Li exchange hierarchical X zeolite (Li-H-X) was prepared by decationization of X zeolite by NH4Cl solution followed by Li exchange and subsequent calcination. NH4-X and Li-X were prepared to compare the results of LiH-X. XRD, FE-SEM, EDS, N2 adsorption-desorption, and micro-/mesoporous volume were performed. The higher mesoporosity was confirmed in Li-H-X due to the framework dealumination during decationization. Static and dynamic sorption capacity of sorbents was evaluated to identify the performance of sorbent. The CO2 and H2 equilibrium adsorption capacity of Li-H-X was found to be 9.6 mmol g-1 and 0.78 mmol g-1, respectively, at 298 K and 20 bar, which was 25 % (CO2) and 30 % (H2) higher than Li-X. Static experimental data were validated using the Langmuir, Freundlich, and Sips models. The CO2 & H2 dynamic sorption capacity of Li-H-X sorbent for binary gas (CO2/H2, 25/75 %) was 4.145 mmol g-1 and 0.258 mmol g-1 at 303 K and 10 bar. The higher sorption capacity of Li-H-X was obtained due to large micro-/mesoporous volume of sorbent, which may allow to access unoccupied sites at higher pressure. This result reveals that micro-/mesoporous structure of zeolite adsorbs significantly higher CO2 from binary gas stream, which can use to separate pure H2 from gas stream.
Keywords: Adsorption; Carbon dioxide; Hydrogen; Microporous-mesoporous; Separation

Reactive distillation configuration for the production of ethyl acrylate - Gore, Jayram I.; Mahajani, Sanjay M.; Mali, Nilesh A. (CHEMICAL ENGINEERING AND PROCESSING-PROCESS INTENSIFICATION, 2024)
Keywords: ACETIC-ACID; CYCLOHEXYL ACETATE; Design; Dimethyl carbonate

Binderless low silica X zeolite for methane separation from binary CO2/CH4 biogas stream: A comprehensive experimental and computational study - Yadav, Tushar R.; Shrotri, Aadesh R.; Kate, Pranjali N.; Devasia, George; Niphadkar, Prashant S.; Mali, Nilesh A.; Krishnamurty, Sailaja; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2025)
This study presents the synthesis of binderless Na-LSX (B-Na-LSX) and binderless NaK-LSX (B-NaK-LSX). XRD, SEM, EDS, and N-2 physisorption were used for characterization of samples. Computational modelling of prepared sorbent was performed for the fundamental understanding of zeolite topology and adsorption behaviour. The breakthrough experiments are used to evaluate the adsorption capacities on CO2/CH4 (40/60 vol%) binary biogas stream. The results were compared with commercial Na-LSX (C-Na-LSX). The breakthrough adsorption capacity of B-Na-LSX was 3.08 mmol g(-1) and 0.29 mmol g(-1) of CO2 and CH4, respectively, at 300 K and 1 bar. CO2 sorption capacity of B-Na-LSX was similar to 11 % and similar to 17 % higher than B-NaK-LSX (2.77 mmol g(-1)) and C-Na-LSX (2.56 mmol g(-1)), respectively. DFT study reveals that the higher adsorption of CO2 over CH4 was attributed to higher charge transfer from CO2 to zeolite framework. Dual-bed six-step Pressure Swing Adsorption (PSA) was performed on B-Na-LSX at 6 bar. similar to 232 cycles were run with above 98 % of CH4 purity and similar to 74 % of recovery. The life-cycle test of sorbent was studied. It was implied that the designed sorbent is effective to produce the high purity of CH4 and can be utilized for a longer period for CH4 production.
Keywords: Binderless; Biogas; LSX zeolite; methane; PSA; Separation

A detailed study on heat of reaction and heat rate determination of nitrobenzene hydrogenation to aniline reaction using power compensation reaction calorimeter - Kumar, Rajendra; Mane, Pradip R.; Shingote, Savita K.; Mali, Nilesh A. (Process Safety Progress, 2025)
The present study reports experimental heat of reaction and heat rate data of nitrobenzene hydrogenation to aniline reaction with process parameter variation. A high-pressure isothermal power compensation reaction calorimeter was used for this work. A systematic and step-by-step procedure is also reported to determine the heat of reaction and heat rate for a highly exothermic reaction. The sensitivity of experimental molar heat of reaction (kJ/mol) and evolved heat rate (W) values for nitrobenzene hydrogenation reaction was analyzed for various important process parameters, such as temperature, pressure, substrate quantity, solvent quantity, catalyst quantity, RPM, and hydrogen feed rate. Nitrobenzene hydrogenation reactions were conducted using ethanol as solvent and 5% Pd/C as a catalyst with 55-65 degrees C temperature and 7-9 Bar absolute pressure range. More than 99.99% conversion of nitrobenzene to aniline was obtained, and no other by-products were found. The average experimental nitrobenzene hydrogenation heat of reaction of 21 different experiments was found to be -581.87 kJ/mol, and the maximum heat rate during the nitrobenzene hydrogenation reaction was found to be 16.16 W for experiments using 10 gm of nitrobenzene in solvent.
Keywords: heat of reaction; heat rate; Hydrogenation; nitrobenzene; power compensation; reaction calorimeter

Feasibility study of reactive chromatography for the synthesis of 2-ethoxyethyl acetate using the amberlyst-15 catalyst - Gore, Jayram I.; Nadeem, Mohd; Mahajani, Sanjay M.; Mali, Nilesh A. (Industrial & Engineering Chemistry Research, 2025)
Reactive chromatography is a promising process intensification technology that combines reaction and separation in a single piece of equipment. In this study, the reaction kinetics and adsorption behavior of esterification of 2-ethoxyethanol (EC) with acetic acid (AcOH) using Amberlyst-15 as a catalyst are studied using batch reactions and reactive chromatography. Batch reactions are performed to study the kinetic behavior, and an appropriate kinetic model is proposed. To evaluate adsorption parameters, nonreactive separation experiments are performed in a fixed bed chromatographic reactor (FBCR), and results are compared with model predictions. Further, the MATLAB simulations are performed for reactive separation using kinetics and adsorption data, and results are validated by the experiments. Experimentally obtained breakthrough profiles of FBCR for reaction and desorption reveal the applicability of reactive chromatography for the synthesis of ethyl cellosolve.

Isobaric vapor-liquid-equilibrium data measurement of toluene with ethyl acetate, n-Propyl Acetate, Iso-propyl Acetate, Iso-butyl Acetate, and Iso-amyl Acetate: experiments and modeling - Sutar, Dipak S.; Mali, Nilesh A.; Ghuge, Pravin D. (Journal of Chemical and Engineering Data, 2025)
The isobaric vapor-liquid equilibrium (VLE) data of the systems (ethyl acetate + toluene), (n-propyl acetate + toluene), (iso-propyl acetate + toluene), (toluene + iso-butyl acetate), and (toluene + iso-amyl acetate) were measured under the isobaric condition at 92 kPa using a glass dynamic recirculation apparatus. The experimental VLE data was correlated by NRTL, Wilson, and UNIQUAC activity coefficient models to account for the nonideality. The binary interaction parameters of the models were obtained by regressing the experimental data using the maximum likelihood objective function. The thermodynamic consistency of the experimental data was checked by using the Van Ness test and the infinite dilution test. Extrapolating the activity coefficient at infinite dilution was done by regressing the experimental data with an extended Redlich-Kister equation. The NRTL, Wilson, and UNIQUAC models exhibited a maximum root-mean-square deviation less than unity for temperature and vapor mole fraction. Additionally, it is worth noting that no azeotrope was identified in the VLE data in this study.